Advancements in vaccine development and therapeutic approaches for severe fever with Thrombocytopenia Syndrome - Ganbold, Tsenddari; Acharya, Satabdi; Sheet, Sunirmal; Munkhtur, Enkhtsatsral; Hong, Seong-Tshool (Frontiers in Cellular and Infection Microbiology, 2025)
Severe Fever with Thrombocytopenia Syndrome (SFTS), caused by the SFTS virus (SFTSV), is a tick-borne disease that poses a significant public health threat due to its high fatality rate and the lack of effective treatments or vaccines. Since its first identification, SFTSV has been reported in multiple countries, including China, South Korea, Japan, and Vietnam, highlighting its expanding regional footprint and potential global impact. This review summarizes recent preclinical and early clinical advancements in vaccine development and therapeutic strategies for SFTSV, with an emphasis on novel vaccine platforms and antiviral approaches. It also discusses the critical role of immunocompromised animal models, such as IFNAR–/– and STAT2–/– mice, in elucidating disease mechanisms and evaluating candidate interventions. Promising vaccine platforms include mRNA-based vaccines, viral vector vaccines, protein subunit vaccines, and inactivated virus vaccines. Additionally, therapeutic approaches—such as RNA-dependent RNA polymerase (RdRp) inhibitors, calcium channel blockers, immunotherapies, targeted therapeutic strategies, and traditional Chinese medicine—have demonstrated potential in preclinical and limited clinical studies. However, challenges remain, including reduced efficacy when treatment is administered late, limited validation in human clinical trials, and the risk of viral resistance. Despite progress, key challenges persist in modeling human SFTS in animals and translating preclinical findings to clinical applications. This review underscores the urgent need for continued research to address these gaps, accelerate the development of effective countermeasures, and enhance global preparedness for future SFTSV outbreaks.